Diversification and control in emerging markets: The case of Chilean firms - Mauricio Jara-Bertin; Felix J. López Iturriaga; Christian Espinosa (BRQ Business Research Quarterly, 2015)
We analyze the effect of two types of corporate diversification (business diversification and ownership diversification) on the market value of the Chilean firms. For a sample of 83 nonfinancial firms listed on the Santiago Stock Market from 2005 to 2013, we find a discount for both business and ownership diversification, which is consistent with that reported for other economic or institutional settings. Second, we find that the business diversification discount is related to the ownership structure and is due to the excess of the largest shareholders' control rights. Third, we find that the ownership diversification discount becomes a premium when the ownership diversification enables the control of the affiliated firms. This effect can be explained by the improvement of internal capital markets that allows overcoming the limitations of Chilean external capital markets."
Keywords: 650; Business diversification; Chile; Emerging Latin-American markets; Ownership structure; Firm value